A comprehensive review on strength properties for making Alccofine based high performance concrete. (2021) - Boobalan, S.C.; Aswin Srivatsav, V.; Mohamed Thanseer Nisath, A.; Pratheesh Babu, A.; Gayathri, V.
Abstract: This paper gives the comprehensive review on the strength properties for making the Alccofine based High Performance Concrete. Various researchers were conducted for incorporating the Alccofine materials with various proportions in High Performance Concrete. Alccofine materials cause concrete to attain high strength at an early stage and has higher durability and workability when compared to regular mix of concrete. Alccofine 1203 is a micro fine mineral additive for concrete and mortars for lowering water demand, and also reduces the heat of hydration, improving the strength and durability parameters of concretes at various ages. This paper has analysed the various research publications for making the efficient Alccofine based High Performance Concrete. Major advantage of Alccofine is low calcium silicate material, which enhances pH of the concrete to protect against corrosion, faster removal of shuttering, better pump ability of concrete and improved durability and reduced permeability of concrete.